Plasminogen activator, tissue type regulates germinal vesicle breakdown and cumulus expansion of bovine cumulus–oocyte complex in vitro†. Issue 6 (2nd April 2019) - Yu, Bo-Yang; Subudeng, Gerile; Du, Chen-Guang; Liu, Zhi-hong; Zhao, Yu-Fen; Namei, Erge; Bai, Yue; Yang, Bing-Xue; Li, Hai-Jun
Abstract: Plasminogen activator, tissue type (PLAT) and its inhibitor serpin family E member 1 (SERPINE1) cooperatively regulate PLAT activity in various reproductive processes. However, it is unknown whether this includes bovine oocyte maturation. We addressed this question in the present study by evaluating PLAT and SERPINE1 protein localization in immature cumulus–oocyte complexes (COCs), as well as PLAT mRNA and protein expression in cultured COCs after 0, 8, 16, and 24 h of in vitro maturation (IVM). We also examined the effects of PLAT and SERPINE1 on germinal vesicle breakdown (GVBD) and oocyte cyclic 3' 5' adenosine monophosphate (cAMP) levels, cumulus expansion index, and expansion-related gene expression in oocytes derived from bovine COCs cultured for 4, 8, and 12 h and in COCs cultured for 16 h. Both PLAT and SERPINE1 localized in cumulus cells but only the latter was detected in oocytes. PLAT and SERPINE1 transcript levels increased during IVM; however, from 8 to 16 h, the levels of PLAT remained stable whereas those of SERPINE1 increased, resulting in a decline in PLAT concentration. Additionally, PLAT delayed GVBD, increased oocyte cAMP levels, and blocked cumulus expansion and associated gene expression, which was reversed by SERPINE1 supplemented. Thus, PLAT delays bovine oocyte GVBD by enhancing oocyte cAMP levels during the first 8 h of IVM; suppression of PLAT activity via accumulation of SERPINE1 in COCs results in cumulus expansion from 8 to 16 h of IVM. These findings provide novel insights into the molecular mechanisms underlying in vitro bovine oocyte maturation. Abstract : Plasminogen activator, tissue type and its inhibitor serpin family E member 1 cooperatively regulate germinal vesicle breakdown and cumulus expansion of bovine cumulus-oocyte complexes in vitro.